Factors Determining High School Students' Growth Mindset in Surakarta: A Thematic Analysis from Educators' Perspectives - Ma'rifatin Indah Kholili; Nandang Rusmana; Ahman Ahman; Nandang Budiman (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This qualitative study explores the factors shaping high school students’ growth mindset from the perspective of educators in Surakarta, Indonesia, a novel approach in the local context. Utilising Focus Group Discussions (FGD) and narrative inquiry, data were collected from 18 school counsellors and 6 Principals/Vice Principals across public and private high schools. Thematic analysis, supported by NVivo software, identified ten key themes. Findings reveal that students’ internal motivation and future goals are the most dominant factors, while the role of parents and family environment emerges as the most prominent external influence. Other contributing factors include self-perception, socioeconomic conditions, school environment, teacher roles, aspirations, and educational policies. These results underscore the crucial synergy between school and family environments, highlighting the need for relevant and challenging educational policies that foster a growth mindset. Practical implications emphasise parental involvement and developing students’ life goals for optimal growth mindset cultivation.